Analisis Kinerja Sosial PT Garuda Indonesia Tbk Berbasis Laporan Berkelanjutan 2024 (Analysis of PT Garuda Indonesia Tbk's Social Performance Based on the 2024 Sustainable Report) - Az Zahrah, Ulfah Syu’latul; Hayati, Risalatul; Leniwati, Driana (STIE Malangkucecwara, 2025)
This study aims to analyze the social performance of PT Garuda Indonesia Tbk in its 2024 sustainability report, with a focus on the fulfillment and protection of human rights. It uses a Systematic Literature Review with content analysis of the report. Data were collected through documentation and analyzed using data reduction, narrative presentation, and conclusion drawing. The findings show major social transformation through the Respectful Workplace Policy, promoting zero tolerance for discrimination and harassment. The company also provides occupational health services and inclusive training to ensure equality. Its commitment to human rights is reflected in support for freedom of association and inclusive recruitment, including people with disabilities. The study affirms the relevance of stakeholder and legitimacy theories in sustainability reporting. In terms of policy, it recommends improving human rights disclosures in state-owned enterprises. The novelty lies in its post-crisis evaluation of human rights-based practices and Garuda Indonesia’s gold rating achievement in ASTRAT 2024.